(untitled) (GESTIÓN Y TENDENCIAS, 2019)
IFRS 16 addresses the identification of lease contracts as well as their accounting treatment in the financial statements of lessees and lessors. This article discusses the identification of the lease contract, measurement challenges, sale and leaseback transactions, and the transition to IFRS 16.